Comparative Analysis of Confucians Teachings Based on Morality and Legalism Based on Legal State Administration - PhD Ikramova Iroda Rikhsivayevna; Jumayev Jobir Shavqi o‘g‘li (Zien Journals, 2024)
The evolution of ancient Chinese philosophy and culture is examined in this article. Additionally, a comparison analysis is conducted between the morality-based Confucianism and the legislation-based Legism, both of which greatly influenced the Chinese people's worldview in ancient China
Keywords: Ancient China; Confucianism; legalism; state administration